Tourism Industry and Community Readiness: A Case Study of the Mandalika Special Economic Zone (KEK) - Muhammad Azizurrohman; Uwi Martayadi; Mohamad Najmudin; Fathurrahim Fathurrahim; I Wayan Bratayasa (Journal of Economics Research and Social Sciences, 2023)
The local community of Kuta Mandalika Village is required to adapt to the regional tourism industry as the spearhead of tourism operations in the Special Economic Zone for Tourism in West Nusa Tenggara. As a result, researchers aim to see how prepared the residents of Kuta Mandalika Village are to welcome tourism to their village. The cognitive, emotional, and conative components all play a role in community readiness. The community at Kuta Mandalika Village was studied using a qualitative research method. In-depth interviews and a non-probability sample strategy were used to identify relevant informants in this study. For the first phase, snowball sampling was chosen as the data collection strategy. According to the findings, the community of Kuta Mandalika Village are well prepared to host tourism activities in the Mandalika Special Economic Zone. However, they are not yet prepared to participate in the tourism industry. The village is in the process of transitioning to a tourism-based society. The phenomena of rapid tourist development pushe the community as hosts, who are directly affected by tourism, to prepare themselves in an indirect way. The government, academics, and the private sector all have a role to play in helping to develop the surrounding community in terms of the capital and skills that the industry requires.